Multi-omics insights into Palmitoylation-mediated brain network remodeling and glioblastoma risk - Shasha Tan; Jinliang You; Huijun Wang; Long Zhao; Shun Li; Xiaoping Tang; Hongjun Liu (Discover Oncology)
Abstract Glioblastoma (GBM) remains a lethal brain tumor with limited therapeutic progress, necessitating novel insights into its molecular drivers. This study investigates the causal role of protein palmitoylation-a post-translational modification regulating tumor metabolism and microenvironment-in GBM pathogenesis through neuroimaging-mediated pathways. Leveraging two-sample Mendelian randomization (MR) and multi-omics data from FinnGen (406 GBM cases/378,749 controls) and UK Biobank (3,935 brain imaging phenotypes), we identified protective effects of palmitoylation-related genes (ZDHHC3: OR = 0.17, 95%CI = 0.0602–0.4824; ZDHHC6: OR = 0.41, 0.2330–0.7267; ZDHHC13: OR = 0.64, 0.4745–0.8618; PPT2: OR = 0.59, 0.3568–0.9843) against GBM risk. Neuroimaging mediation analysis revealed that 15–23% of this protection operates through structural and functional brain remodeling, including reduced parahippocampal volume (mediated 15.96% for ZDHHC13), diminished default mode network connectivity ICA100 edge 295, and ICVF Body of corpus callosum(15.29% mediation for ZDHHC6). Bidirectional regulation was observed in motor pathways, where palmitoylation genes simultaneously suppressed corticospinal tract integrity (FA) and enhanced cortical plasticity. Sensitivity analyses confirmed robustness (Cochran’s Q p > 0.05; MR-PRESSO global test p > 0.05), with Steiger filtering excluding reverse causation. Our findings suggest that palmitoylation may play a key modulatory role in GBM risk through influencing brain network dynamics, highlighting neuroimaging features (e.g., DMN connectivity, parahippocampal atrophy) as potentially informative for GBM risk and warranting further investigation for their role in early detection. These results also raise the possibility of palmitoylation-targeted therapies aimed at disrupting tumor-microenvironment crosstalk, suggesting a direction for future therapeutic exploration.